Integrasi Autodesk Revit Dan Plugin Sofistik Dalam Penerapan Bim Untuk Efisiensi Pembuatan Bar Bending Schedule (BBS) - Ramadhan, Farhan Kurnia; Hidayat, Benny (Universitas Andalas, 2025)
The application of Building Information Modeling (BIM) is increasingly important in the construction industry because it can improve efficiency, accuracy, and collaboration. One aspect that is greatly influenced by BIM is the preparation of the Bar Bending Schedule (BBS), a detailed document regarding the quantity, dimensions, shape, and weight of steel reinforcement in reinforced concrete elements. Manual preparation of the BBS tends to be time-consuming and produces significant waste material due to suboptimal cutting. This study aims to analyze the application of Autodesk Revit integrated with the Sofistik plugin in creating the BBS and compare it with conventional methods. The case study was conducted on the construction project of the Lecturer Room Building and Multipurpose Room of the Faculty of Cultural Sciences, Andalas University. Data were obtained from Detailed Engineering Drawings (DED), material specifications, and interviews with contractors. The research stages include three-dimensional structural modeling, verification with clash detection, reinforcement modeling, BBS creation using Revit–Sofistik, and optimization of 12-meter-long reinforcing bar cutting using Excel Solver. The research results show that conventional methods require five to six weeks, while Revit–Sofistik only takes three weeks, or even two weeks, from the reinforcement stage to the BBS output, with a time efficiency of 45–66 percent. Bar cutting optimization can reduce material waste to below three percent. These findings prove that the Revit–Sofistik integration can accelerate the BBS process while reducing material waste, even though the cutting optimization function is not yet fully integrated into the BIM flow.